Biologia dos coléteres foliares em Rubiaceae de cerrado e floresta estacional semidecídua do estado de São Paulo - Tresmondi, Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Colleters are responsible for the secretion of mucilaginous or resinous substance, usually associated with the protection of the meristem and developing organs against desiccation and damage by pathogens, herbivores, and also with the formation of bacterial leaf nodes. Additional compounds such as alkaloids, lipids and phenolic compounds may be present in the secretion of colleters. Variations in the composition to indicate the specificity and subcellular mechanisms for synthesis and release of colleters secretion of different species. In Rubiaceae colleters can be classified as: standard, reduced standard, intermediate, brush-like, winged, filiform, dendroid and lacrimiforme. This study compared 17 species of Rubiaceae occurring in savanna and semi-deciduous forest. Were evaluated morphology, distribution and histochemistry of stipular colleters using optical and scanning electron microscopy. To evaluate the subcellular mechanisms of the secretory cells of colleters eight species were selected with standard colleters with variation in the nature of secretion, which were subjected to analysis in a transmission electron microscope using conventional and cytochemical techniques - ZIO for marking endomembrane systems, osmium-imidazole for unsaturated lipids and polysaccharides to Thiéry. Moreover, in situ monitoring was performed microclimate, budding period and proportion of new leaves damaged apices on both ecosystems throughout a year. Among the 17 species studied, 14 showed colleters standard with variation in the distribution and size. The secretion varied from predominantly hydrophilic, mixed to predominantly lipophilic. This secretion variation reflected in differences in the populations of organelles between species, mainly on the number and appearance of plastids, endoplasmic reticulum and dictyosomes including vesicles associated with these. Secretion accumulation sites were evident in the outer periclinal wall of epithelial ...

Coléteres são estruturas responsáveis pela secreção de substância mucilaginosa ou resinosa, geralmente associados com a proteção ao meristema e aos órgãos em desenvolvimento contra dessecação e danos por patógenos, herbívoros, e ainda, com a formação de nódulos bacterianos foliares. Compostos adicionais como alcaloides, compostos fenólicos e lipídios podem estar presentes na secreção dos coléteres. As variações na composição indicam especificidade na função e nos mecanismos subcelulares de síntese e liberação da secreção dos coléteres de diferentes espécies. Em Rubiaceae os coléteres variam quanto à morfologia podendo ser classificados como: padrão, padrão-reduzido, intermediário, filiforme, escova, dendroide e lacrimiforme. Neste estudo foram comparadas 17 espécies de Rubiaceae ocorrentes em cerrado e floresta estacional semidecídua. Foram avaliadas morfologia, distribuição e histoquímica dos coléteres estipulares usando microscopia óptica e eletrônica de varredura. Para avaliação dos mecanismos subcelulares das células secretoras dos coléteres, foram selecionadas oito espécies com coléteres padrão com variação na natureza da secreção, as quais foram submetidas a análises em microscópio eletrônico de transmissão com uso de técnicas convencionais e citoquímicas - ZIO para marcação do sistema de endomembranas, ósmio-imidazol para lipídios insaturados e Thiéry para polissacarídeos. Além disso, foi realizado acompanhamento in situ do microclima, período de brotamento de novas folhas e proporção de ápices danificados em ambos os ecossistemas ao longo de um ano. Dentre as 17 espécies estudadas, 14 apresentaram coléteres padrão com variação na distribuição e no tamanho. A secreção variou de predominantemente hidrofílica, mista ou predominantemente lipofílica. Esta variação refletiu em diferenças nas populações de organelas entre as espécies, principalmente,...
Biology of leaf colleters in cerrado Rubiaceae and forest semideciduos the state of São Paulo
Keywords: Rubiácea; Secreção; Ultraestrutura (Biologia); Coléteres; Plantas dos cerrados; Rubiaceae